Desain Kemasan Sebagai Strategi Branding Produk Cokelat Bali - Sari, Ni Luh Desi In Diana (Seni Media Rekam ISI Surakarta, 2011)
Efforts to make Balinese chocolate products of IKM sector as souvenirs for tourists require branding strategy to improve the image of the product in the minds of the target audience. Branding strategies conducted through designing of logo as a brand identity, packaging design as a media product appeal and POP (Point of Purchase) as a means of product promotion. The creative concept refers to the main idea of